Work motivation history, theory, research, and practice - Latham, Gary P. 1945- (SAGE Publications, Inc., 2016)
'Work Motivation' draws on the author's experiences as a staff psychologist in, and a consultant to, organizations. It is written with a 'mentor voice' that is highly personal and rich in examples, including enduring influences of mentors on researchers in the field
Keywords: Personnel - Motivation; Employee motivation; Arbeitsmotivation